Strategy for the detection and differentiation of Mycobacterium avium species in isolates and heavily infected tissues - Moravkova, M; Hlozek, P; Beran, V; Pavlik, I; Preziuso, S; Cuteri, V; Bartos, M (Research in veterinary science, 2008)
The members of Mycobacterium avium species, comprising M. avium subsp. paratuberculosis, M. a. hominissuis, M. a. avium, M. a. silvaticum, are currently the most prevalent opportunistic pathogenic mycobacteria causing mycobacterial infection in animals and humans. The ability to distinguish between these subspecies is of relevance for proper diagnosis and control programmes of the diseases. The aim of this study was to design a fast and specific PCR strategy for the detection and differentiation of M. avium subspecies from the solid plate cultures for use in routine veterinary diagnosis. We have developed a multiplex PCR based on IS900, IS901, IS1245 and the dnaJ gene. This method allows the detection of M. a. paratuberculosis, M. a. hominissuis and M. a. avium/M. a. silvaticum in one PCR reaction and theoretically enables mixed infections of M. a. paratuberculosis and M. a. avium or M. a. paratuberculosis and M. a. hominissuis to be revealed. The sensitivity of this multiplex PCR is 10(3)CFU for each bacterial strain in one PCR reaction, which also enabled the use of this test directly for DNA isolated from the tissue of the heavily infected sheep.
Keywords: senzitivita a specificita; Mycobacterium Infections; polymerázová řetězová reakce; DNA, Bacterial; mykobakteriózy; DNA bakterií; Animals; Polymerase Chain Reaction; Sheep; ovce; nemoci ovcí; Sheep Diseases; Mycobacterium avium; zvířata; Sensitivity and Specificity